Transformasi Metode Pembelajaran Pendidikan Agama Islam: Studi Kasus di Pesantren Al Islam Tenggulun Solokuro Lamongan Pasca Tragedi Bom Bali - Afif Afandi; Ibnu Habibi; Ahsan Hakim (Jurnal Pendidikan Indonesia, 2026)
The 2002 Bali Bombing tragedy had significant social and institutional impacts on Islamic boarding schools (pesantren), particularly in relation to the stigma of radicalism and demands for reform in Islamic education systems. In this context, the teaching of Islamic Religious Education (PAI) no longer operates within a neutral pedagogical space but becomes an arena of adaptation to social and ideological pressures. This study aims to analyze the transformation of PAI teaching methods at Pesantren Al Islam Tenggulun, Solokuro, Lamongan, in the aftermath of the Bali Bombing tragedy. The research employs a qualitative approach with a case study design, utilizing in-depth interviews, participant observation, and document analysis. The findings indicate that the transformation of PAI teaching methods occurred gradually while maintaining traditional pesantren methods such as sorogan and bandongan, which were later integrated with dialogical and contextual learning approaches. This transformation serves as a pedagogical response to post-terrorism stigma, as well as an institutional strategy by the pesantren to foster a religious orientation among students that is moderate, inclusive, and contextual. These findings contribute theoretically to the study of Islamic education by demonstrating that the transformation of PAI teaching methods in pesantren functions as a pedagogical adaptation strategy in responding to post-terrorism social pressures.